Developing a code of conduct for a small Finnish company - Hara, Siina (2018)
In response to various business ethics scandals, companies face growing pressure to prove the ethicality of their business conduct. Ethical business practices is not expected only from large corporations, but from all companies regardless of their size or the industry in which they operate. In globalized markets, national legislation has limited power to control business ethics. In addition, stakeholders’ expectations on ethical business conduct often go beyond the law. A growing number of companies has voluntarily engaged in various activities of business ethics management in order to meet the legal requirements and stakeholders’ expectations. Code of conduct is one of the most widely applied tools for business ethics. The aim of this thesis is to present the development process of a code of conduct for a case company. In line with stakeholder theory and the concept of organizational culture, eight members of the case company were interviewed on the company values and current practices on the most common business ethics issues. Themes for the interviews were based on the topics covered in well- known international initiatives for business ethics, including UN Global Compact, OECD Guidelines for Multinational Enterprises, the Caux Round Table Principles and SA8000–standard, and they were supplemented with issues that are commonly addressed in codes of conduct. The suggested code of conduct was drafted using a “code pyramid”, a framework for code of conduct developed by Kaptein (2008). The contents of the code are in line with the abovementioned international initiatives for business ethics. The contents of the suggested code are primarily based on the interviewees’ perceptions of the case company’s values and current practices, which were completed with some business ethics topics that are most commonly addressed in codes of conduct.